Sintilimab: A Promising Anti-Tumor PD-1 Antibody - Zhang, Lin; Mai, Wuqian; Jiang, Wenyang; Geng, Qing (Frontiers in Oncology, 2020)
Sintilimab (Tyvyt®) is a monoclonal antibody against programmed cell death protein 1 (PD-1). It could block the interaction between PD-1 and its ligands, and help the anti-tumor effect of T-cells to recover. Sintilimab is developed by Innovent Biologics and Eli Lilly and Company, and has been approved to treat relapsed or refractory classical Hodgkin lymphoma in patients who have undergone 2 or more lines of systemic chemotherapy by National Medical Products Administration of China. Recently, sintilimab has been reported in plenty of literature and shows satisfying anti-tumor effect. Meanwhile, there are some reports showing the side effects of it. Overall, sintilimab has similar anti-tumor effects and a better safety profile compared to nivolumab and pembrolizumab in Hodgkin lymphoma, natural killer/T cell lymphoma and advanced non small cell lung cancer. In this review, we aim to briefly describe the mechanisms, pharmacological characteristics, anti-tumor effects, predictive parameters of efficacy and side effects of sintilimab, providing valuable information of sintilimab for decision-making in the treatment of tumors in the future.